The "EU Climate Bank"? - A study on the environmental commitments of the European Investment Bank and the alignment with the right to a healthy environment - Georg,Emelie (2022)
This thesis examines the relationship between international finance and environmental rights, and how the concept of sustainable finance has emerged as a response to climate change and the rapid transition towards a sustainable economy. Multilateral development banks (MDBs) are a key player in the transition to a green economy, contributing to 68% of global climate finance. Thus, MBDs are the majority deliverer of public climate finance. In terms of loan volumes, the European Investment Bank (EIB) constitutes the biggest multilateral lender in the world and operates as the lending arm of the European Union. The EIB has put itself in the centre of the transition to a sustainable economy as it announced itself as the “EU climate bank” when adopting its latest environmental strategy, the EIB Group Climate Bank Roadmap 2021-2025 (CBR). This thesis aims to examine how the EIB has incorporated environmental and human rights concerns into its lending activities, and the alignment of its internal environmental policies with international human rights standards on the right to a healthy environment. To achieve this overarching aim, the thesis examines the human rights obligations to the right to a healthy environment. The unclear human rights obligations on the right to a healthy environment are emphasized, especially focusing on the uncertainties related to international organisations such as the EIB. These uncertainties stem from the distinct and versatile features of the EIB, as it constitutes an EU institution but also an independent MDB, thereby holding characteristics of a private commercial entity. However, a closer examination has shown that the EIB is obliged to fulfil both substantive and procedural obligations related to the right to a healthy environment due to its position as an EU institution.
Keywords: European Investment Bank; the right to a healthy environment; multilateral development banks; international financial institutions; human rights; sustainable finance; the EIB Group Climate Bank Roadmap 2021-2025